Composition united: improving articulation between two-year and four-year colleges - Lee, Kari, author; Frank, Katherine, advisor; Souder, Donna, committee member; Eskew, Doug, committee member (Colorado State University. Libraries, 2011)
In 1977, Mina Shaughnessy posed what she believed was an "embarrassingly rudimentary question"-- "What goes on and what ought to go on in the composition classroom?" (320). Over thirty years later, the answer to this question still remains under intense debate as educators struggle to maintain their distance from the K-12 standards and still ensure that students are receiving an equitable education at ever institution of higher learning. This thesis argues for improved articulation between composition programs in two-year and four-year colleges in the same community as a partial solution to this debate, advocating for a collaborative model as opposed to the increasingly popular competitive model for university operations. Two-year and four-year in the same community need to work together in order to ensure that students are receiving the same key concepts in their education, regardless of their place of enrollment. This will also illustrate academia's dedication to students' success and counter gainsayers arguing that there is another agenda. Finally, this thesis proves that, by increasing articulation and fostering communication, the overall structure of composition programs will be strengthened. This heightened dialogue between educators will allow them to learn from colleagues with different areas of expertise and strengthen areas of weakness. It will aid in successful assessment and professional development, and, ultimately, our institutions of higher learning will produce more confident, successful writers.
Keywords: articulation; two-year college; composition